Roles of exogenous and endogenous FGF-2 in animal models of depression - Jarosik, Jarek; Legutko, B.; Werner, S.; Unsicker, Klaus; von Bohlen und Halbach, O. (Restorative neurology and neuroscience, 2011)
Purpose: Several members of the fibroblast growth factor (FGF) family have been shown to be dysregulated in individuals with major depression, and treatment with antidepressants has been reported to increase FGF-2 mRNA levels in the forebrain. Methods: We have used the tail suspension test (TST), and olfactory bulbectomy (OBX), and FGF-2 deficient mice to investigate putative roles of FGF-2 as an antidepressant and mediator of antidepressive drug actions. Results: FGF-2 applied intraventricularly generated antidepressant-like effects in the TST. FGF-2, similar to the antidepressant amitriptyline, attenuated neuron demise in the piriform cortex and posterolateral cortical nucleus of the amygdala following OBX. Moreover, OBX induced reduction in hippocampal neurogenesis could be ameliorated by subsequent treatment with either amitriptyline or FGF-2. Furthermore, FGF-2 was effective in reversing depressive-like behavior induced by OBX, monitored in the locomotor activity and the passive avoidance test. In bulbectomized FGF-2 deficient mice, treatment with amitriptyline protected neurons, but failed to reverse behavioral alterations. Conclusions: Together, these results suggest that FGF-2 constitutes both a potential target for antidepressive treatments and an important growth factor in the cytokine network underlying the actions of antidepressive drugs. The results further suggest a requirement of endogenous FGF-2 for mediating behavioral, but not neuroprotective actions of amitriptyline.
Gesehen am 04.07.2022